Human amniotic fluid mesenchymal stem cells attenuate pancreatic cancer cell proliferation and tumor growth in an orthotopic xenograft mouse model - Chen, Ying-Cheng; Lan, Ying-Wei; Huang, Shiaw-Min; Yen, Chih-Ching; Chen, Wei; Wu, Wan-Ju; Staniczek, Theresa; Chong, Kowit-Yu; Chen, Chuan-Mu (Stem cell research & therapy, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is a malignant cancer and chemotherapy ineffectively treats PDAC, leading to the requirement for alternative tumor-targeted treatment. Human amniotic fluid mesenchymal stem cells (hAFMSCs) have been revealed to suppress tumor growth in various cancers and they are a strong candidate for treating PDAC. To evaluate the effects of hAFMSCs on human pancreatic carcinoma cells (PANC1, AsPC1 and BxPC3 cell lines) and the possible mechanism involved, an in vitro cell coculture system was used. A PANC1 orthotopic xenograft mouse model was established and hAFMSCs were injected intravenously at 4 weeks post-xenograft. An in vitro coculture assay showed that hAFMSCs inhibited PANC1 cell proliferation by inducing S phase cell cycle arrest and increased cell apoptosis in a time-dependent manner. In PANC1 cells, hAFMSCs caused the downregulation of Cyclin A and Cyclin B1 as well as the upregulation of p21 (CDKN1A) at 24 h post coculture. The upregulation of pro-apoptotic factors Caspase-3/-8 and Bax at 24 h post coculture reduced the migration and invasion ability of PANC1 cells through inhibiting the epithelial-mesenchymal transition (EMT) process. In a PANC1 orthotopic xenograft mouse model, a single injection of hAFMSCs showed significant tumor growth inhibition with evidence of the modulation of cell cycle and pro-apoptotic regulatory genes and various genes involved in matrix metallopeptidase 7 (MMP7) signaling-triggered EMT process. Histopathological staining showed lower Ki67 levels in tumors from hAFMSCs-treated mice. Our data demonstrated that hAFMSCs strongly inhibit PDAC cell proliferation, tumor growth and invasion, possibly by altering cell cycle arrest and MMP7 signaling-triggered EMT.
Gesehen am 09.01.2024